Assessment of the Kinetic Trajectory of the Median Nerve in the Wrist by High-Frequency Ultrasound - Yi-Hsun Lin; Mei-Yu Hsieh; Fong-Chin Su; Shyh-Hau Wang (Sensors, 2014)
Carpal tunnel syndrome (CTS) is typically diagnosed by physical examination or nerve conduction measurements. With these diagnostics however it is difficult to obtain anatomical information in the carpal tunnel. To further improve the diagnosis of CTS, an attempt using 30 MHz high-frequency ultrasound to noninvasively detect the local anatomical structures and the kinetic trajectory of the median nerve (MN) in the wrist was explored. Measurements were performed on the right wrist of 14 asymptomatic volunteers. The kinetic trajectory of the MN corresponding to flexion (from 0° to 90°) and extension (from 90° to 0°) movements of the fingers were detected by a cross correlation-based motion tracking technique. The average displacements of the MN according to finger movements were measured to be 3.74 and 2.04 mm for male and female subjects, respectively. Moreover, the kinetic trajectory of the MN in both the ulnar-palmar and total directions generally follows a sigmoidal curve tendency. This study has verified that the use of high-frequency ultrasound imaging and a motion tracking technique to sensitively detect the displacement and kinetic trajectory of the MN for the assessment of CTS patients is feasible.